Pkm Group of Housewives in Bube Baru Village, Suwawa District, Bone Bolango District, Gorontalo Province - Borolla, Hendrik David Julianus; Arda, Zul Adhayani (Universitas Nusantara PGRI Kediri, 2019)
The new village of Bube is one of the villages in Suwawa District, Bone Bolango Regency, Gorontalo Province. The village of Bube Baru is located about 12 km from the capital city of the Province whose average population works as farmers and breeders. Housewives in Bube Baru Village generally do not work, they only act as housewives. This causes them to have quite a lot of free time after doing routine tasks as housewives. Based on the above, it is necessary to have an activity or training program that can improve knowledge and also the standard of living of the people of Bube Baru village through the empowerment of housewives in Bube Baru Village. The people of Bube Baru village generally have yard that has not been used optimally. The Community Partnership Program (PKM) which will be conducted in Bube Baru Village, Suwawa District, Bone Bolango District, aims to empower housewives in utilizing home yards through planting of family and vegetable medicinal plants (TOGAS). This PKM activity also aims to improve health, fulfill nutrition and living standards of the people in Bube Baru Village, Suwawa District. The method implemented in the PKM Program is counseling, training and experimentation through the making of a demonstration of the use of home yards for TOGAS. Partners are groups of housewives who have been formed consisting of two groups and have agreed to participate in all activities programmed into the PKM to be implemented. PKM activities will be carried out for eight months, since March to October 2018. Outcomes of PKM activities in the form of increased knowledge and skills of housewives through the use of home yards as a place for family and vegetable medicinal plants (TOGAS) that can improve the health and living standards of the people in the village Bube Baru District of Suwawa.